A temperature-responsive selenium nanohydrogel for strawberry grey mould management. Issue 27 (24th June 2022) - Liu, Yanan; Huang, Yuqin; Liu, Jiawei; Liu, Jie
Abstract : The synthesis of an Ipr@MSe@LA nanoplatform was illustrated and its antifungal activity with temperature-responsive release in vitro and in potted strawberries was studied. Abstract : Grey mould is a fungal disease caused by Botrytis cinerea ( B. cinerea ), which can cause serious damage to a variety of crops. Herein, we developed iprodione (Ipr) reagent-loaded mesoporous selenium nanoparticles (MSe NPs), combined them with low-melting agarose (LA), and obtained a temperature-responsive selenium particle nanogel (Ipr@MSe@LA NPs) using a simple method. Importantly, Ipr@MSe@LA could capture B. cinerea and quickly be softened to realize the controlled release of Ipr, and effectively inhibit and kill B. cinerea . Plate-based antibacterial tests showed that the colony area of the Ipr@MSe@LA NPs was 4.27 cm −2, which was much smaller than that of the control (25 cm −2 ). In addition, the Ipr@MSe@LA NPs showed good biocompatibility, and they could improve the photosynthetic efficiency of plants and promote plant growth. Measurement of the fluorescence parameters showed that the maximum photochemical efficiency ( F v / F m ) of the plant leaves of the inoculated group ( B. cinerea ) is 0.58, but the F v / F m value of the Ipr@MSe@LA group is higher than 0.8. In particular, Ipr@MSe@LA NPs could prolong the storage time of strawberries, thereby preserving their freshness. Overall, Ipr@MSe@LA NPs exhibit excellent effects in terms of controlling strawberry gray mould and prolonging the fruit storage time, and this is expected to become a promising strategy for developing intelligent pesticide formulations.